Аspekts of culturologic competency and skills in the system of preparation of specialists in koledz cultures and arts - M. V. Panius (History of science and technology, 2015)
The article is devoted to solving of the urgent need of the entirely – integrating considering of the process of knowledge in the course of preparing of specialist of high school. It is founded one of the effective ways of decision of this task – the formation of the system of culturologic competency and skills  throw installing of integrating culturologic model.